Genome‐wide meta‐analysis of age‐related cognitive decline in population‐based older individuals. (31st December 2021) - Acharya, Vibha; Fan, Kang‐Hsien; Snitz, Beth E; Ganguli, Mary; DeKosky, Steve; Lopez, Oscar L.; Feingold, Eleanor; Kamboh, M. Ilyas
Abstract: Background: Cognitive decline is a major characteristic of aging and neurogenerative diseases such as Alzheimer's disease (AD), Parkinson's disease and other dementias. With worldwide increases in life‐expectancy and elderly population, cognitive decline is a major public health concern. Understanding genetic contributors to age‐related decline in cognition may facilitate identification of the molecular mechanisms of cognitive decline. Method: To discover genetic influences on cognitive decline, we conducted genome‐wide meta‐analyses on longitudinal performance of five cognitive domains (attention, language, executive function, visuospatial, memory) and the global domain, constructed from five domains, using 3068 individuals aged 65 and above across three longitudinal cohorts: the Gingko biloba Memory Evaluation Study (GEMS), Monongahela‐Youghiogheny Healthy Aging Team (MYHAT) and Monongahela Valley Independent Elders Survey (MoVIES). A linear mixed effect model was used to find individual specific slopes by adjusting for baseline age, years of education and sex. Results: APOE*4 (rs429358), a well‐known risk factor for AD, demonstrated a genome‐wide significant association with the memory (P= 1.37E‐09) and global (P= 9.26E‐10) domains. Previous studies have also reported APOE*4 's association with memory decline. In addition to APOE*4, multiple suggestive associations of gene loci with cognition were also observed for each domain as follows: attention on chromosome 9 near RASEF / FRMD3 (P = 8.29E‐08), memory on chromosome 6 near ID4 / MBOAT1 (P = 1.27E‐07), visuospatial function on chromosome 11 near PAMR (P = 2.74E‐07), language on chromosome 9 near PSAT1 (P = 4.08E‐07), executive function on chromosome 4 near SNHG27 (P = 6.49E‐07), and global function on chromosome 4 near LINC00290 (P=8.80E‐07). Conclusion: Our result suggests that in addition to APOE, multiple genetic loci affect cognitive decline in older individuals. These findings may offer new insights into understanding the genetic architecture of cognitive decline.